UPDATING THE STATISTICAL REGISTER OF HOUSING IN THE REPUBLIC OF MOLDOVA USING OPEN-SOURCE GIS TECHNOLOGIES - Spataru, Mihail; Vlasenco, Ana; Nistor-Lopatenco, Livia; Grama, Vasile (Journal of Engineering Science (Chişinău), 2022)
his article describes the possibilities of promoting and implementing open-source geoinformation technologies in the field of statistical activity in the Republic of Moldova, which will simplify and streamline the process of analysis, collection, systematization of data, as well as their dissemination. Since 2019, the National Bureau of Statistics of the Republic of Moldova, according to the recommendations of the United Nations, has proposed the creation of the geo-coded Statistical Register of Housing (SRH). With the creation of the National Spatial Data Infrastructure (NSDI), this goal can be achieved, as SRH will form the basis of the Population and Housing Census (PHC) from the 2020 round. The geospatial data from SRH will be used to delimit the census enumeration areas, and the reviewed population will be attached to the geographical coordinates of the dwelling. These enumeration areas will cover the entire territory of the Republic of Moldova and will serve to plan human resources, organize field activities and ensure the full coverage of census units (for people, households and dwellings).